New critical spaces in transitional justice : gender, art, and memory - Kurze, Arnaud; Lamont, Christopher K. (Indiana University Press, 2019)
Gathering work from contributors in international law, political science, sociology, and history, New Critical Spaces in Transitional Justice explains current trends in responses to post-conflict and post-authoritarian nations and offers original empirical research to help define the field for the future.